“Estudio epidemiológico de enfermedades bucales prevalentes en escolares de 6 a 12 años. I.E. N° 88240, Nuevo Chimbote. 2018” - Colonia Quiros, Ruth karla (2019)
ABSTRACT The purpose of this basic and descriptive cross-sectional study was to determine the prevalence of oral diseases in schoolchildren aged 6 to 12 years of the I.E. No. 88240, New Chimbote, 2018. The study sample consisted of 222 schoolchildren aged 6 to 12 years included by proportional stratified random sampling; A clinical examination was performed, the information was performed on a data collection form. The data obtained were analyzed in SPSS v24. The prevalence of dental caries predominated from 6 to 9 years (57.6%) in the female sex (53.2%). The severity of dental caries was very high with a CPOD / ceo-d of 8.8 with a higher percentage in the age of 6 to 9 years (24.3%), predominantly female (22.1%). The prevalence of malocclusion was 6 to 9 years (45.1%) with class I malocclusion in the female sex (38.7%). The prevalence of oral diseases in schoolchildren is mostly presented in the group of 6 to 9 years of the I.E. No. 88240, Nuevo Chimbote, 2018; according to dental caries it was 89.6% and Class I malocclusion was 69.4%.